Constructing Victimhood: Storied Opposition to Legislation Protecting LGBTQ Students - Lai, Daniel; Presser, Lois; Schally, Jennifer L. (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2019)
Contemporary initiatives against anti-LGBTQ bullying in the United States include enumeration policies, which name sexual orientation as an unacceptable basis for bullying. Conservative opposition to these and other initiatives has been swift, taking discursive and specifically narrative form. This article examines how opponents of prevention and intervention use narrative to resist efforts to curb anti-LGBTQ bullying, based on analysis of 22 public statements challenging anti-bullying legislation. They deny anti-LGBTQ bullying’s impact and reassign victimizer and victim positions. Achieving justice for anti-LGBTQ bullying victims requires recognition of the stories that uphold heteronormative power.